“FACTORS ASSOCIATED WITH MUSCULOSKELETAL DISORDERS (MSDS) COMPLAINTS AMONG PALM OIL HARVESTERS” - Siti Aisyah; Siti Maisyaroh Fitri Siregar; Yulizar Kasma; Yarmaliza; Fakhrurradhi Lutfhi (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2025)
Repetitive motions, poor posture, and overuse injuries may lead to musculoskeletal diseases (MSDs), which manifest as pain in the muscles, joints, and tendons. The physical demands, frequent motions, and reliance on hand tools put palm oil harvesters at a higher risk of developing MSDs than other types of workers. The purpose of this research was to identify causes of work-related injuries (MSDs) reported by palm oil harvesters in North Sumatra's PTPN IV Regional I Sei Putih. The method used was quantitative and cross-sectional in nature. Using complete sampling, 34 participants were chosen for the survey. Nordic Musculoskeletal Questionnaire (NMQ) was used for data collection. The data were examined with the use of univariate and bivariate approaches, with a significance threshold of p < 0.05, utilizing the Chi-square and Fisher's Exact tests. Aging (p = 0.000), length of service (p = 0.001), and smoking behaviors (p = 0.002) were shown to be significantly associated with complaints of MSDs. The correlation between BMI and the outcome was not statistically significant (p = 0.704). There was a strong correlation between age and complaints of MSDs. Companies should prioritize the implementation of ergonomic programs and frequent health monitoring as preventative measures for MSDs, particularly for employees aged 35 and above who have been with the company for at least five years, according to these results. It is also important to improve health education on the dangers of smoking. To get stronger and more thorough findings, further study with a bigger sample and deeper analysis is needed.